0385 Children, Adolescents, and Their providers: the Narcolepsy Assessment Partnership (CATNAP™) Pediatric Narcolepsy Registry: Baseline Demographics. (25th May 2022) - Macfadden, Wayne; Leary, Eileen; Gwadry-Sridhar, Femida; Owens, Judith
Abstract: Introduction: Limited information is available on the natural history, presentation, and management of pediatric narcolepsy. CATNAP™ is a retrospective/prospective, longitudinal, multicenter, web-based pediatric narcolepsy registry (NCT04899947). The primary objectives are to improve understanding of the natural history of pediatric narcolepsy, characterize symptom presentation and diagnosis, and understand treatment practices and outcomes. Methods: Eligible children/adolescents (<18 years) had confirmed narcolepsy. Using web-based portals, patients, caregivers, and clinicians completed an initial survey on sociodemographic characteristics; diagnostic, medical, and treatment history; comorbidities; and disease progression. Results: Patient/caregiver-reported interim baseline data are included (N=25 patients; mean±SD age: 15.6±2.9 years; 52.0% female; 60.0% White; 64.0% narcolepsy type 1 [NT1]; 28.0% narcolepsy type 2; mean±SD age at narcolepsy diagnosis: 11.0±4.0 years). At narcolepsy diagnosis, the percentages of participants who were <10, 10 to 15, and ≥16 years of age were 36.0%, 52.0%, and 12.0%, respectively. Symptoms at first diagnosis included excessive daytime sleepiness (EDS; 96.0%), cataplexy (64.0%), disrupted sleep (64.0%), vivid dreams (52.0%), and nightmares (40.0%). Comorbid psychiatric disorders were present in 36.0% of participants and included anxiety disorder (20.0%), depression (16.0%), attention-deficit/hyperactivity disorder (ADHD; 12.0%), and panic attacks (8.0%). Misdiagnosis of narcolepsy was reported in 32.0% of participants; alternative diagnoses included anxiety disorder, ADHD, sleep apnea (all 8.0%), and obsessive-compulsive disorder (4.0%). Physician specialties that confirmed narcolepsy diagnosis included neurologists and pediatricians (each 24.0%), pulmonologists (16.0%), pediatric neurologists (12.0%), general practitioners/internists (8.0%), and endocrinologists (4.0%). In participants with NT1 (n=16), warning symptoms for cataplexy were reported by 43.8% and included a sense that cataplexy was imminent without physical symptoms, a sense that time had somewhat suspended, fear/fright, and a feeling of warmness (all 6.3%). At diagnosis, the number of cataplexy episodes per day in order of frequency was 2 (37.5%), 3 (25.0%), 4 (18.8%), and 1 (12.5%). Current medications for narcolepsy included stimulants (60.0%), wake-promoting agents (40.0%), sodium oxybate (32.0%), serotonin-norepinephrine reuptake inhibitors (16.0%), and selective serotonin reuptake inhibitors (8.0%). Conclusion: Interim baseline data from CATNAP provide valuable information on the experience and management of pediatric narcolepsy that will facilitate education of patients and caregivers, inform clinical decision-making, and potentially improve treatment strategies. Support (If Any): Jazz Pharmaceuticals.